My first experience with academic research - Atanasova, Viktoria (Journal for German and Scandinavian Studies / Списание „Германистика и скандинавистика“, 2024)
The subject of the research was the German phraseme construction [von A (N1) so viel verstehen wie X von Y (N2)]. Fixed realizations of this construction include, for example, von A so viel verstehen wie der Hahn vom Eierlegen/ wie die Kuh vom Radfahren/ wie die Kuh vom Sonntag/ wie die Kuh vom Schachspielen.